Supporting Impact Evaluation Studies in Water Supply and Sanitation in India - World Bank (Washington, DC, 2015)
This synthesis report details the process, outputs and intermediate outcomes Technical Assistance (TA) ‘supporting impact evaluation studies in water supply and sanitation in India (P144956)’ implemented by the World Bank’s Water and Sanitation Program (WSP). The TA supported the design and implementation of impact evaluations in water and sanitation projects in India and also facilitated data driven analytical work and capacity building. Specific contributions of the TA are the following: enabling monitoring and evaluation, enabling policy, and enabling institutions. In the context of the significant challenges India is facing in water and sanitation access and the extreme complexity of the institutional systems for the provision of water supply and sanitation, the access to flexible yet practical analytical assistance at the point of need is highly valued by government counterparts. This TA on supporting water supply and sanitation has identified the need for a larger regional or global activity that can carry forward impact evaluations in the sector and produce global knowledge that will serve as a public good for the client countries. The TA also underscored the importance of upstream analytical work and replication of results in different contexts as well as the need to develop customizable tools and instruments for faster implementation of data collection efforts. Above all, the TA emphasized the need to invest in expanding local capacity in designing and implementing rigorous impact evaluations so that more evidence could emerge in the coming years for better policy formulation in the water and sanitation sector.